Is Adherence to the Mediterranean Diet Associated with Healthy Habits and Physical Fitness? a Systematic Review and Meta-Analysis Including 565,421 Youths - Garcia-Hermoso, A (Cambridge University Press, 2022)
The relationship between adherence to the Mediterranean diet (MD), physical activity (PA), sedentary behaviour and physical fitness levels has been analysed in several studies; however, there is mixed evidence among youth. Thus, this study aimed to meta-Analyse the associations between adherence to the MD, PA, sedentary behaviour and physical fitness among children and adolescents. Three databases were systematically searched, including cross-sectional and prospective designs with a sample of healthy youth aged 3-18 years. Random effects inverse-variance model with the Hartung-Knapp-Sidik-Jonkman adjustment was used to estimate the pooled effect size (correlation coefficient (r)). Thirty-nine studies were included in the meta-Analysis, yielding a total of 565Â 421 youth (mean age, 12·4 years). Overall, the MD had a weak-To-moderate positive relationship with PA (r 0·14; 95 % CI 0·11, 0·17), cardiorespiratory fitness (r 0·22; 95 % CI 0·13, 0·31) and muscular fitness (r 0·11; 95 % CI 0·03, 0·18), and a small-To-moderate negative relationship with sedentary behaviour (r-0·15; 95 % CI-0·20,-0·10) and speed-Agility (r-0·06; 95 % CI-0·12,-0·01). There was a high level of heterogeneity in all of the models (I 2 ≥ 75 %). Overall, results did not remain significant after controlling for sex and age (children or adolescents) except for PA. Improving dietary habits towards those of the MD could be associated with higher physical fitness and PA in youth, lower sedentary behaviours and better health in general. ©